Reduced mental workload of neonatal intensive care unit nurses through a self-designed education class: A randomized controlled trial - Maryam Mohamadi; Mahboobeh Namnabati; Akram Aarabi (Wolters Kluwer Medknow Publications, 2019)
Background: One of the factors affecting the behavior and performance of nurses is mental workload. Training programs can improve the attitude, knowledge, and performance of nurses. However, the impact of these programs on mental workload is not clear. Therefore, the study aimed to evaluate and compare the effect of two conventional and self-designed education classes on the mental workload of neonatal intensive care unit (NICU) nurses. Materials and Methods: This study was conducted on 68 nurses, divided into two intervention and control groups. Subjects of the intervention group attended a social awareness reinforcement class, in which one of the dimensions of emotional intelligence was introduced and covered. Research tool was the mental workload questionnaire of National Aeronautics and Space Administration Task Load Index (NASA-TLX). Results: In this research, results of the paired t-test were indicative of a significant decrease in the mean score of mental workload immediately after the intervention (t = 1.48, p < 0.001) and one month later (t = 1.11, p = 0.007). Moreover, a significant difference was observed in the mean score of mental workload of the intervention group between before and after the conventional education class, and before and 1 month after the self-designed class using repeated-measures analysis of variance (F = 21.31, p < 0.001). Conclusions: According to the results of the study, the conventional education class had no impact on the mental workload, whereas the self-designed class significantly decreased mental workload. Therefore, it is suggested that education programs be conducted for NICU nurses to improve their emotional intelligence, which leads to decreased level of mental workload.